2013
DOI: 10.1128/mbio.00573-13
|View full text |Cite
|
Sign up to set email alerts
|

Fc Gamma Receptor 3A Polymorphism and Risk for HIV-Associated Cryptococcal Disease

Abstract: Cryptococcus neoformans is one of the most common causes of fungal disease in HIV-infected persons, but not all of those who are infected develop cryptococcal disease (CD). Although CD4+ T cell deficiency is a risk factor for HIV-associated CD, polymorphisms of phagocytic Fc gamma receptors (FCGRs) have been linked to CD risk in HIV-uninfected persons. To investigate associations between FCGR2A 131 H/R and FCGR3A 158 F/V polymorphisms and CD risk in HIV-infected persons, we performed PCR-based genotyping on ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 67 publications
1
70
0
1
Order By: Relevance
“…In this context, it is interesting to note that Rohatgi et al very recently reported that a higher-affinity variant of the phagocytic receptor FcγRIIIA is a risk factor for HIV-associated cryptococcal disease (26). Thus, both host factors (26) and pathogen factors (this study) that enhance phagocytic uptake appear to increase the risk of (severe) cryptococcal disease.…”
Section: Figurementioning
confidence: 95%
“…In this context, it is interesting to note that Rohatgi et al very recently reported that a higher-affinity variant of the phagocytic receptor FcγRIIIA is a risk factor for HIV-associated cryptococcal disease (26). Thus, both host factors (26) and pathogen factors (this study) that enhance phagocytic uptake appear to increase the risk of (severe) cryptococcal disease.…”
Section: Figurementioning
confidence: 95%
“…C. neoformans has an antiphagocytic polysaccharide capsule (6) which requires the presence of opsonins in the form of complement or capsule-binding antibodies (Ab) for phagocytosis to occur (3). Fc receptor polymorphisms were associated with susceptibility to C. neoformans (7,8), suggesting a link between phagocytosis and the outcome of infection. Once inside the macrophage, the fungus resides in a mature phagosome and can survive acidification and phagocytic bursts (4,9).…”
mentioning
confidence: 99%
“…Yapılan birçok çalışmada FcγRIIIa V/V polimorfizminin F/F fenotipine göre yanıtının daha iyi olduğu, yine FcγRIIa H/H fenotipinin R/R fenotipine göre yanıtlarının daha iyi olduğunu bildiren yayınlar mevcuttur (8,9,12). Ancak daha sonraki birçok araştırıcı, bahsedilen bu fenotiplerin hastalıksız yaşam üzerine etkisi olmadığını bildirdiler (20)(21)(22)(23)(24)(25)(26)(27)(28). Ayrıca daha önceki çalışmalardaki araştırıcılar belirtilen fenotiplerde yanıtın nasıl iyi olduğuna dair bir yorumda bulunmamışlardır.…”
Section: Discussionunclassified